Plyometric training for physical education university students - Eyzaguirre-Maldonado, Edwin Hector; Reynaga-Chavez, Rusbita; Jeri, Yuri Gutierrez; Huamani, Oscar Gutierrez; Huaman-Romani, Yersi-Luis (International Journal of Innovative Research and Scientific Studies, 2024)
The purpose of this research is to analyze and describe the plyometric training of university students in the professional career of physical education. The design is non-experimental, cross-sectional of the descriptive type whose approach is of the quantitative type. The data collection was done through an intentional online survey in which 885 university students participated and responded to eight items voluntarily and anonymously. The results show that university students who practice sports have the desire to want to represent their institution for which they use various plyometric methods for their workouts or daily routines in an informal way that keeps them in a competitive physical state at a regional or national level but not for a competition at an international level. Conclusion. University students perform their own workouts because they believe they have experience in training which is false that is, they themselves create their own daily routines without a professional trainer. They also need an adequate place equipped with trainers with experience in national or international competitions to improve their physical performance. This research has implications for the students because they have to adapt to the rhythm of plyometric exercises to be fit in any national or international competition and the implications for the teachers are that they must take into account which competition they want to participate in to be able to train them as appropriate.